2022
DOI: 10.1097/j.pain.0000000000002601
|View full text |Cite
|
Sign up to set email alerts
|

Amygdalar functional connectivity during resting and evoked pain in youth with functional abdominal pain disorders

Abstract: Youth with functional abdominal pain disorders exhibit altered amygdalar connectivity after a visceral pain induction task associated with changes in pain unpleasantness and pain intensity. Differences in amygdalar connectivity in youth with functional abdominal pain disorders were also observed at rest when compared with that in healthy youth.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
20
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(20 citation statements)
references
References 80 publications
0
20
0
Order By: Relevance
“…Similar seed-based connectivity analyses can be carried to other brain regions. In addition to examining functional connectivity to the amygdala, we will also calculate the network connectivity of the 17 functional networks defined in the atlas developed by Yeo et al [24], which is based on rs-fMRI datasets from 1,000 healthy young adults as part of our exploratory analysis. Since pain is a heterogenous experience with multiple networks involved, we will explore these 17 networks broadly and also anticipate specific patterns of change emerging for the default mode network [1] defined in this atlas. 3D Pulse Arterial Spin Labeling ( 3D PASL) sequence at a perfusion mode of FAIR QII (5 min 24 sec) will be used to measure regional CBF [30, 31].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Similar seed-based connectivity analyses can be carried to other brain regions. In addition to examining functional connectivity to the amygdala, we will also calculate the network connectivity of the 17 functional networks defined in the atlas developed by Yeo et al [24], which is based on rs-fMRI datasets from 1,000 healthy young adults as part of our exploratory analysis. Since pain is a heterogenous experience with multiple networks involved, we will explore these 17 networks broadly and also anticipate specific patterns of change emerging for the default mode network [1] defined in this atlas. 3D Pulse Arterial Spin Labeling ( 3D PASL) sequence at a perfusion mode of FAIR QII (5 min 24 sec) will be used to measure regional CBF [30, 31].…”
Section: Methodsmentioning
confidence: 99%
“…To assess if changes in functional connectivity and brain activations following ADAPT will correspond to reductions in pain (intensity and unpleasantness) and anxiety ratings. Our previous research has indicated amygdalar functional connectivity changes in youth with FAPD undergoing water loading are evident when accounting for changes in pain intensity and pain unpleasantness [1].…”
Section: Introductionmentioning
confidence: 99%
“…Functional abdominal pain disorders (FAPD) are among the most common chronic pain conditions impacting children and adolescents. These complex pain conditions are thought to result from dysregulations in the brain-gut axis and are characterized by aberrant amygdalar functional connectivity patterns when experiencing pain during a water loading symptom provocation task (WL-SPT), and at rest when compared to healthy youth [ 1 ]. The prevalence of such conditions ranges from 4% to 41% globally and the median rate is approximately 12% [ 2 ].…”
Section: Introductionmentioning
confidence: 99%
“…ADAPT was found to be superior in reducing symptoms of functional disability and anxiety in youth with FAPD in a randomized clinical trial as compared to standard medical treatment alone [ 14 ]. Although the study team has previously found evidence of aberrant functional connectivity in the brains of youth with FAPD [ 1 ] (during the WL-SPT and when compared to the brains of healthy youth), the potential neural correlates underlying effective treatments for these conditions are unknown. This is important because it allows us to understand whether an effective nonpharmacologic treatment for pain and anxiety impacts neurological functioning in youth with FAPD.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation